Examining the Effectiveness of INAC Funding - Tsao, Marcus (Université d'Ottawa | University of Ottawa, 2017)
The Aboriginal population in Canada performs significantly below the national average in socioeconomic measures such as education, employment, and income. Indigenous and Northern Affairs Canada spent $5.6 billion in 2006 and $8.4 billion in 2015 towards improving these factors. This paper examines the relationship between INAC funding and socioeconomic outcomes using a regression discontinuity design (RDD). I utilize the border between two geographical zones, with First Nations bands located above 50 degrees latitude receiving more funding than First Nations bands below. Observations were categorized along two metrics: (i) within 50km, 100km, or 150km from the boundary, and (ii) divided into 200km or 400km segments along the boundary. On average, First Nations bands above 50° latitude receive $6,400,153 and bands below 50° latitude receive $4,583,365. The results show that there is no significant relationship between INAC funding level and individual income level, high-school attainment rate, unemployment rate and number of households requiring minor repairs.